What are the key factors contributing to the inequity in healthcare resource allocation? Evidence from China’s health panel data from 2009 to 2021 - Dong, Enhong; Wang, Tingting; Xu, Ting; Chen, Xueting; Zhou, Qianqian; Gao, Weimin; Liu, Yuping (Frontiers in Public Health, 2025)
BackgroundAs economic growth drives higher demand for health services, equitable health resource allocation becomes crucial to meet diverse healthcare needs. Since China’s reform and opening-up, increased government healthcare investment has not fully resolved regional disparities. Existing studies, often relying on methods other than the concentration index, fail to comprehensively analyze the link between resource inequities and economic factors. This study uses the concentration index and its decomposition to assess regional disparities and identify determinants of inequity, offering practical recommendations for optimizing resource distribution in China and similar developing nations.MethodsThis study analyzed China’s healthcare resource allocation (institutions, beds, and workforce) from 2009 to 2021 using the concentration index to measure equity across socio-economic regions and its decomposition method to identify contributing factors to inequality.ResultsFrom 2009 to 2021, the numbers of institutions per 1,000 people (IPK), beds per 1,000 people (BPK), doctors per 1,000 people (DPK), technicians per 1,000 people (TPK), and nurses per 1,000 people(NPK) in China increased. The concentration index (CI) for IPK remained negative, while BPK’s CI turned negative after 2013. CIs for DPK, TPK, and NPK stayed positive. The CI for IPK’s absolute value rose, while others decreased. Factors like population size (PS), population density(PD), geographical Location(GL), maternal mortality rate(MMR), rate of born-baby weighting less than 2.5 kg (RBWL25), and perinatal mortality rate (PMR) influenced unequal healthcare resource distribution, with PS and RBWL25 favoring developed areas, and PD, GL, and MMR favoring less developed regions. Additionally, urbanization level (UL), Out-of-Pocket (OPP), per capita health expenditures(PCHE), per capita gross domestic product(PCGDP), disposable income of urban residents(DIUR), government health expenditures (GHE), and number of insured(NI) positively impacted resource allocation to developed provinces, with varying effects.ConclusionThis study analyzes 2009–2021 panel data, revealing growth trends and regional disparities in China’s healthcare resource equity, focusing on institutions, beds, and workforce. Need variables (PS, PD, and RBWL25) reduced bed/doctor disparities, while MMR/PMR worsened maternal/nurse inequities. Non-need economic factors concentrated resources in affluent areas despite redistribution efforts. The findings highlight ongoing challenges in equitable distribution and offer crucial policy insights for China and other developing nations.